“Determinación del ciclo biológico e indice de predicación de chrysoperla externa sobre huevos de sitotroga cerealella, en laboratorio, en Tarapoto región San Martín” - Bartra Ramirez, Anderson (2006)
In order to Determining the biological cycle of Chrysoperla externa Haguen in the Entomology Laboratory of the UNSM and to Evaluate the behavior and the capacity of predation of Chrysoperla externa over six different dose of Sitotroga cerealella's eggs we excuted it in breeding lnsects Laboratory of Agrarian Sciences Faculty of the University National of San Martín among January to April of 2005 to a temperature average of 28,47ºC and relative humidity of 83,23%. For this work the experimental design was used totally at random(DCA), (dose of eggs of Sitotroga cerealella: 0,003; 0,005; 0,007; 0,009; 0,011 and 0,013 g) with six treatments and five observations. The results demonstrated that bigger food dose it is reduced the larval phase 1 and 11 to 2,24 and 3, 19 days. In the larval phase 111 it became short with the smail dose. The biggest size in the larva 1 and 11 of the externa/ Chrysoperla were obtained with the dose T6 (0,013 g), with an average of 3,24 and 4,40 '·mm respectively; in the 111 larval phase the T4 (0,009 g) with an average of 7,20 mm it reached the biggest size. The precocious death of the adults of externa/ Chrysoperla was due sinse to the starvation these they didn't prefer the given food Sitotreoga cerealel/a's eggs. The biological cycle of the externa/ Chrysoperla (from egg until the adult's death) fed with eggs of Sitotroga cerea/el/a under laboratory conditions it was of 29,36. With a longevity of 2,29 days to externa/ Chrysoperla which make possible keep the breeding module, because doesn 't carry out the reproductive period.